The Development of Competency-based Online Course for Course for Improving Literacy of Ecological Civilization - Yisa, Yu; Makpa, Piyawadee; Pujeeb, Nuttida (Journal of Cultural Analysis and Social Change, 2025)
This study investigates the ecological civilization literacy of Visual Communication Design majors in Zhejiang Province. It develops a competency-based online curriculum to strengthen students’ knowledge, skills, and values related to sustainable design. Using an explanatory sequential mixed-methods design, the research was conducted in five stages: diagnostic analysis, needs assessment, competency modeling, curriculum development, and expert-guided iterative optimization. Quantitative data were collected from 336 students and 307 graduates, revealing a structurally imbalanced profile characterized by strong ecological attitudes, moderate conceptual understanding, and weak behavioral competence. Qualitative data from faculty (n = 24), employers (n = 25), and experts (n = 24) further indicated fragmentation in current ecological instruction, misalignment between educational supply and industry requirements, and a strong demand for project-based and context-relevant learning experiences. Based on Delphi consultation and content analysis, the study constructed the “Three Dimensions–Nine Competencies” ecological civilization literacy model, which integrates ecological knowledge, sustainable design skills, and value-oriented professional ethics. Guided by Competency-Based Education (CBE) and backward design principles, an online course titled Ecology and Vision: Integrating Sustainable Design Competencies was developed. The curriculum comprises 64 hours across four modules, incorporating localized Zhejiang case studies, interdisciplinary resources, PBL-driven rural revitalization projects, learning analytics, and diversified assessment aligned with the K–S–V competency framework. Expert review demonstrated the curriculum's high validity and feasibility (IOC averages 0.89–0.95; satisfaction scores 4.3–4.6/5). Through iterative refinement, the final model presents a scalable pathway for integrating ecological civilization education into design disciplines. The study contributes a theoretical framework, a methodological model, and a practical solution to advancing sustainability-oriented design education in Chinese higher education institutions. It also provides a transferable curriculum development paradigm for other regions and disciplines seeking to integrate ecological civilization into professional training.